Anxiety symptoms in young people with autism spectrum disorder attending special schools: Associations with gender, adaptive functioning and autism symptomatology. (April 2016) - Magiati, Iliana; Ong, Clarissa; Lim, Xin Yi; Tan, Julianne Wen-Li; Ong, Amily Yi Lin; Patrycia, Ferninda; Fung, Daniel Shuen Sheng; Sung, Min; Poon, Kenneth K; Howlin, Patricia
Anxiety-related problems are among the most frequently reported mental health difficulties in autism spectrum disorder. As most research has focused on clinical samples or high-functioning children with autism spectrum disorder, less is known about the factors associated with anxiety in community samples across the ability range. This cross-sectional study examined the association of gender, age, adaptive functioning and autism symptom severity with different caregiver-reported anxiety symptoms. Participants were caregivers of 241 children (6–18 years old) with autism spectrum disorder attending special schools in Singapore. Measures included the Spence Children's Anxiety Scale and assessments of overall emotional, behavioural and adaptive functioning. Caregivers reported more anxiety symptoms in total, but fewer social anxiety symptoms, than Spence Children's Anxiety Scale Australian/Dutch norms. There were no gender differences. Variance in total anxiety scores was best explained by severity of repetitive speech/stereotyped behaviour symptoms, followed by adaptive functioning. Severity of repetitive speech/behaviour symptoms was a significant predictor of separation anxiety, generalized anxiety, panic/agoraphobia and obsessive–compulsive subscale symptoms, but not of social phobia and physical injury fears. Adaptive functioning and chronological age predicted social phobia and generalized anxiety symptoms only. Severity of social/communication autism symptoms did not explain any anxiety symptoms, when the other variables were controlled for. Findings are discussed in relation to the existing literature. Limitations and possible implications for prevention, assessment and intervention are also discussed.